Rebranding as an Economic Strategy: Linking Brand Transformation to Customer Satisfaction and Organizational Performance in the Banking Industry - Melayanto, Yanuedi; Berlianto, Margaretha Pink (International Journal of Economics Development Research (IJEDR), 2025)
To compete, the banking industry needs to make various innovations, one of which is re-branding its brand. This study aims to investigate the effect of the rebranding strategy conducted by KB Bukopin on customer satisfaction and performance. The quantitative method was used, involving 187 respondents in the Jabodetabek area who were customers of KB Bank. The population of this research is KB Bank customers. The results showed that band personality and brand elements affect performance and satisfaction, while brand identity only has a positive effect on brand performance. The band name has no effect on satisfaction and performance. Satisfaction affects trust but has no effect on performance. Trust was also found to have no effect on performance in this context. This research successfully adds to the literature on brand strategy theory. The managerial implications of KB Bank's rebranding suggest that changing name, personality, and brand elements will directly improve satisfaction and performance.